Use of Fetal Echocardiography for Characterization of Fetal Cardiac Structure in Women With Normal Pregnancies and Gestational Diabetes Mellitus. (1st August 2014) - Garg, Salil; Sharma, Prafull; Sharma, Divyesh; Behera, Vineet; Durairaj, Manuel; Dhall, Anil
Abstract : Objectives: To assess fetal cardiac structure and function and to evaluate the efficacy of routine fetal echocardiography for detection of fetal cardiac abnormalities in women with normal pregnancies and those with gestational diabetes mellitus. Methods: In this prospective study, we studied fetal cardiac structure and function in 294 uncomplicated singleton pregnancies and 302 pregnancies complicated by gestational diabetes. Fetal echocardiography (2‐dimensional sonography and pulsed wave Doppler imaging) was used to assess functional parameters and to detect any cardiac structural abnormality. Data from clinical and echocardiographic evaluations of neonates at birth and 3 months were obtained to confirm the antenatal findings. Results: The mean maternal age ± SD was 28.9 ± 5.0 years in the diabetes group and was comparable to that of women with normal pregnancies. The mean hemoglobin A1c value was 6.3%, and the mean body mass index was 28.0 kg/m 2 . The systolic function as assessed by the ejection fraction increased significantly in the diabetes group compared to the normal pregnancy group independent of glycemic control ( P < .001). The pulsed wave parameters (early diastolic peak flow velocity and early‐to‐late diastolic peak flow velocity ratio) were significantly different between the groups ( P < .001). The interventricular septum and fetal ventricular wall thicknesses were significantly increased in the presence of gestational diabetes ( P < .001). No major fetal cardiac structural anomaly was detected in either group. On follow‐up after delivery, all neonates were assessed clinically and by transthoracic echocardiography to rule out congenital defects. Conclusions: In our study, significant increases in the interventricular septum and ventricular wall thicknesses were detected in the presence of gestational diabetes mellitus. Interestingly, none of the neonates of pregnant women with gestational diabetes were found to have echocardiographic evidence of congenital heart disease.